The Effect of Burnout on Turnover Intention with Job Satisfaction as an Intervening Variable - Nuraini, Nuraini; Astiena, Adila Kasni; Lita, Ratni Prima (Newinera Publisher, 2025)
Pharmaceutical personnel are a very important part of health services in hospitals. Based on a preliminary study at three private hospitals in Padang City, it was found that the turnover of pharmaceutical personnel reached 14.8-19.6% in the last three years. Severe burnout, low job satisfaction and increased turnover intention among pharmaceutical personnel which still receive little attention in the literature. The purpose of this study is to determine the effect of burnout on turnover intention mediated by job satisfaction in pharmaceutical personnel in five private hospital pharmaceutical installations in Padang City. The design of this study was cross-sectional by sampling using a questionnaire involving 118 respondents consisting of pharmacists and pharmaceutical technical personnel. The research data was analyzed using Structural Equation Modelling Partial Least Squares (SEM-PLS) and the results of the study were obtained. Job satisfaction significantly mediates the effect between burnout and turnover intention. Burnout and job satisfaction have a significant effect on turnover intention. Burnout has a significant effect on job satisfaction. Demographic factors do not have a significant effect on burnout and job satisfaction. Job satisfaction significantly mediates the influence between demographic factors and turnover intention. Burnout did not significantly mediate the influence between demographic factors and turnover intention. Based on the results of the study, burnout and job satisfaction affect turnover intention. Therefore, the hospital can determine a burnout management strategy and maintain good job satisfaction to prevent an increase in actual turnover.